Soursop Pectinesterase: Extraction, Purification, Properties and Effect on Cloud Stability of Soursop Juice - Misman, Siti Arbaisah (1996)
The presence of pectinesterase in citrus fruit particularly in cloud loss of citrus juice is one of the most intensively studied problems in food technology. However, current reports concerning this enzyme in tropical fruit such as soursop fruit are limited. This project was carried out to study the soursop pulp pectinesterase and its effect on cloud stability of soursop juice. Statistical methods namely fractional factorial design and response surface methodology were applied in experimental design in order to establish optimum conditions for the pectinesterase extraction procedure. Optimum extraction of soursop pectinesterase was obtained using 1.92 M NaCI solution of pH 8.4. Two forms of pectinesterases called PE I and PE II were purified to a single band of protein on SDS PAGE using the techniques of ammonium sulphate fractionation, ion exchange chromatography and gel filtration. PE I had a specific activity of approximately 4 units/mg achieving of purification 43 fold and that of PE II was 6.4 units/mg (229 fold of purification).These pectinesterases PE I and PE II had an approximate molecular weights of 29, 100 and 24, 100 Dalton, respectively as estimated by gel filtration. Comparing their electrophoretic mobilities with those of standard proteins using denaturing electrophoresis, a molecular weight of 31,000 and 28,000 Dalton for PE I and PE II were obtained, respectively. The optimum temperature for enzymic activity was 60 °C for both PE I and PE II. The activation energies of PE I and PE II were calculated as 36 kJ/mol˚K and 42 kJ/mol˚K respectively. The optimum pH for both pectinesterases lie within the range of pH 7.5-8.0. The Km value for PE I was 0.52mg/ml of substrate and 0.0843 mg/ml of substrate for PE II. PE I had a maximum velocity (V max) of 154 units/mg protein and PE II had a V max value of 726 units/mg protein respectively. The logarithmic values of decimal reduction times plotted against temperature had a classic biphasic pattern featuring a sudden change in slope at a temperature exceeding 60°C. Thermal stability data showed that PE I was more thermostable than PE II in the buffer of pH 7.5.D values at 65°C were approximately 5.8 min and 3.4 min for PE I and PE II, respectively. The PE I and PE II possesses Z value of 8.5°C and 8.6°C, respectively. There were less than 1% loss of activity of these enzymes after a year's storage in 0.02 M phosphate buffer pH 7.5 and storage temperature of 4°C.Both enzymes were also tested positive for their ability to destabilize soursop juice cloud at 5 °C and 30°C. Cloud destabilization by PE I occurred the fastest (large decrease in absorbance at 660nm) in the natural juice at 30°C.